How frequently do prices change? Evidence based on the micro data underlying the Belgian CPI - Luc Aucremanne; Emmanuel Dhyne (National Bank of Belgium, 2004)
This paper examines the degree of price rigidity in Belgian consumer prices, using a large database. As to the observed degree of rigidity, the results reveal a substantial amount of heterogeneity, not only across but also within product categories. While prices turn out to be perfectly flexible for some product categories, they tend to be very sticky for others. Each month, nearly 17 p.c. of the consumer prices change on average and the median duration of a price spell is close to 13 months. A substantial subset of our results is compatible with state-dependent pricing, while other results suggest that some timedependency exists as well. The majority of price changes are price increases, but price decreases are not uncommon, except for services. The size of price changes is important. Price changes do not seem to be highly synchronised across price-setters within relatively homogenous product categories.
Keywords: D21; D40; E31; 330; consumer prices; price rigidity; state-dependent pricing; time-dependent pricing; staggered pricing; Verbraucherpreisindex; Preisrigidität; Belgien